2015
DOI: 10.1155/2015/892502
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Dynamics for Integrated Analysis of Accident Sequences considering Uncertain Events

Abstract: The analytical/deterministic modelling and simulation/probabilistic methods are used separately as a rule in order to analyse the physical processes and random or uncertain events. However, in the currently used probabilistic safety assessment this is an issue. The lack of treatment of dynamic interactions between the physical processes on one hand and random events on the other hand causes the limited assessment. In general, there are a lot of mathematical modelling theories, which can be used separately or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Methods based on the integration of probabilistic modeling and T-H modeling have been proposed to evaluate the effects of the uncertain parameters on the performance of passive safety systems and on the evolution of accident scenarios in Nuclear Power Plants (NPPs) (Di Zio, 2014;Alzbutas, 2015). Sampling approaches like Latin Hypercube Sampling (LHS) and Subset Sampling (Turati et al, 2017;Turati et al, 2018;Zio, 2008) have been useful and shown to achieve high reliability estimation accuracy while reducing the number of T-H codes runs (Zio and Pedroni, 2010;Zio and Pedroni, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Methods based on the integration of probabilistic modeling and T-H modeling have been proposed to evaluate the effects of the uncertain parameters on the performance of passive safety systems and on the evolution of accident scenarios in Nuclear Power Plants (NPPs) (Di Zio, 2014;Alzbutas, 2015). Sampling approaches like Latin Hypercube Sampling (LHS) and Subset Sampling (Turati et al, 2017;Turati et al, 2018;Zio, 2008) have been useful and shown to achieve high reliability estimation accuracy while reducing the number of T-H codes runs (Zio and Pedroni, 2010;Zio and Pedroni, 2012).…”
Section: Introductionmentioning
confidence: 99%